Myocardial function and hemoglobin oxygen affinity during hyperglycemia in the fetal lamb. - Bard, H; Fouron, J C; De Muylder, X; Ducharme, G; Lafond, J S (The Journal of Clinical Investigation, 1986)
To determine the effects of maternal hyperglycemia on fetal hemodynamic and cardiac function, a study was carried out on nine chronically catheterized fetal sheep. In six fetuses, glucose was infused intravenously with an initial dose of 5 mg/kg per min. Data were compared with controls. This dose was gradually increased to 16 mg/kg per min by the fifth day. The initial blood glucose was 14.7 +/- 3.0 mg/dl and increased to 54.6 +/- 16.4 mg/dl by the last day of the infusion period (P less than 0.001). The PO2 decreased from a baseline of 20.25 +/- 3.40 to 15.88 +/- 5.24 mmHg (P less than 0.01). Similarly significant decreases were also observed for the blood O2 content and O2 hemoglobin saturation: 8.5 +/- 1.7 to 6.4 +/- 2.2 ml/dl and 62.3 +/- 13.6 to 46.1 +/- 17.6%, respectively, during hyperglycemia (P less than 0.01). The duration of the preejection period (PEP) before the start of the experiment was 45 +/- 4 ms; a final value of 57 +/- 10 ms was obtained (P less than 0.01). However, the electromechanical delay and ejection time (ET) showed no significant variation. The ratio of the PEP/ET increased from 0.31 +/- 0.04 to 0.38 +/- 0.07 (P less than 0.01) during hyperglycemia. The reticulocytes increased from 1.4 +/- 1.8 to 3.1 +/- 2.9% (P less than 0.05) and the 2,3-diphosphoglycerate decreased from 4.4 +/- 1.1 to 2.8 +/- 1.2 mumol/g hemoglobin (P less than 0.005). This study demonstrated that fetal hyperglycemia depresses myocardial function in the fetal lamb. The changes in cardiac function could not be explained by the small drop in O2 saturation.